WAWASAN LINGKUNGAN DAN PEMBANGUNAN BERKELANJUTAN: Studi Kasus Atas Penganugerahan Penghargaan Program Sekolah Adiwiyata Nasional di SMK Negeri 3 Manokwari - Lebang, Yohanes Ada’; Sumule, Agus; Manusawai, Jacob (Universitas Papua, 2018)
The development always has positive and negative sides as environmental problem caused by population growth, technology development and cultural. Environmental problem also caused by the low of the community perspective how to manage the natural resources sustainable. Adiwiyata is a program of the Indonesia Environment Ministry in order to encourage the knowledge and awareness community school for environment preservation. The Public Vocational high School (SMK) Negeri 3 Manokwari is a sample of the Adiwiyata School that follow the Adiwiyata program. This study aimed to analyze the school community knowledge level about environmental concept and sustainable development, also to analyze the education of community knowledge and sustainable development through Adiwiyata program. This study run for a month. Totally, 64 respondents were involved consisting of 1 head school, 23 teachers, 4 staffs, 6 school committees and 30 students that took randomly 10 students each level of class. The Adiwiyata program in SMK Negeri 3 Manokwari was analyzed through scored on each dimensional for multidimensional scaling. Thewhole school community are quite knowledgeable on environmentally sustainable development. The perception map about Adiwiyata program aspects and school community knowledge about sustainable development that grouped into positive and negative groups. The positive group there are policy and curriculum base on environment, while the negative group are the activity base on participatory and management of the environment friendly tool. The value of Stress and R2 are 0.09932 (9.932 %) and the model is appropriate, while the R2 value are 0.89672 (89.672 %) that claim the appropriate model have been achieved.